Factors associated with older adults' perception of health risks of hot and cold weather event exposure: A scoping review - Ratwatte, Priyanjali; Wehling, Helena; Kovats, Sari; Landeg, Owen; Weston, Dale (Frontiers in Public Health, 2022)
Introduction: Hot and cold weather events are increasingly becoming a global burden resulting in premature and preventable morbidity and mortality, particularly in vulnerable groups such as older people and people with chronic health conditions. However, risk perception regarding weather is generally poor among vulnerable groups which often acts as a barrier to the uptake of critical health-protective behaviours. A more cohesive understanding of determinants of risk perception is needed to inform public health risk communication and behaviour change interventions that promote protective health behaviours. This scoping literature review aimed to understand factors influencing perception of personal health risks in vulnerable groups as a result of exposure to hot and cold weather events. Methods: A five-stage scoping review framework was followed. Searches were run across Medline, PsychInfo, Web of Science and EMBASE. Papers were included if they provided rationale for risk perceptions in vulnerable groups in indoor/domestic environments and focussed on samples from OECD countries. Results: In total, 11 out of 5,345 papers met the full inclusion criteria. The majority of papers focused on hot weather events: one study exclusively examined cold weather events and one study addressed both cold and hot weather events. Included papers focused on older adults aged 65+ years. The papers identified seven factors that were associated with older adults’ personal health risk perception of hot and cold weather events: 1) Knowledge of the relationship between hot/cold weather and health risks, 2) presence of comorbidities, 3) age and self-identity, 4) perceived weather severity, 5)past experience with weather, 6) misconceptions of effectiveness of protective behaviours, and 7) external locus of control. Conclusions: Future research should explore risk communication methods by implementing the identified risk perception determinants from this review into health protection interventions targeting older adults. Further understanding is needed regarding risk perceptions in non-elderly vulnerable groups, for examples individuals with chronic diseases or disabilities.